Magnitude of multidrug-resistant and extended-spectrum β-lactamase-producing gram-negative bacteria from tracheal aspirates of intensive care unit patients in Ethiopia - Zenebe Gebreyohannes Berhe; Shambel Araya Haile; Gadissa Bedada Hundie; Ashenafi Alemu Wami; Tesfa Addis; Elias Alehegn; Mahlet Abayneh; Shalom Tsegaye Zergaw; Natnael Dejene Engida; Alganesh Gebreyohanns; Firehiwot Workneh; Tsedale Woldu Hadgu; et al. (PLoS ONE, 2025)
Background Globally, multidrug-resistant (MDR) and extended-spectrum β-lactamase-producing (ESBL)Gram-negative bacterial pathogens are causing significant public health problems, particularly in intensive care units (ICUs) among patients on mechanical ventilation. The objective of the study was to identify Gram-negative bacterial pathogens from tracheal aspirates, determine the prevalence of MDR, and assess the prevalence of ESBL production among the isolates. Methods A hospital-based cross-sectional study was conducted at St. Paul’s Hospital Millennium Medical College (SPHMMC). A total of 181 ICU patients on mechanical ventilation from January to August of 2022 were included. Tracheal aspirates were collected using consecutive sampling techniques, and the samples were inoculated on chocolate, blood, and MacConkey agar plates. Conventional biochemical tests were used to identify Gram-negative bacteria, and antimicrobial susceptibility testing (AST) was carried out via the Kirby–Bauer disc diffusion method. The production of ESBL was confirmed by the combination disc method. The data were entered and analyzed using SPSS version 25 software. Results In this study, 181 study participants were enrolled, with an age distribution ranging from 1 year to 81 years and a median and mode of 15 years and 1 year, respectively. The overall prevalence of Gram-negative bacteria was 65.2%. A total of 189 Gram-negative bacteria were found, of which 52 (44.1%) showed a single organism and 66 (55.9%) were multiple organisms. Of the 189 isolates, 69.8% were MDR, while 86.8% were ESBL producers. Acinetobacter species (50.8%) and Klebsiella pneumoniae (29.6%) were the predominant isolates, with MDRs of 78.1% and 71.4%, respectively, and ESBLs of 100% and 82.1%, respectively. Conclusions A high magnitude of MDR and ESBL was detected. In addition, there was high resistance to cephalosporin-class antibiotics, which is concerning. The MDRs Acinetobacter spp. and K. pneumoniae were the predominant isolates. Regular monitoring of antimicrobial resistance levels, implementing antimicrobial stewardship, and an effective infection control program should be strengthened.